Synthesis, in Silico Study and Biological Evaluation of N-(Benzothiazol/Thiazol-2-yl)benzamide Derivatives as Quorum Sensing Inhibitors against Pseudomonas aeruginosa - Sharma N.; Srivastava N.; Kaushal A.; Das B.; Vashistha A.; Kumar L.; Kumar R.; Kumar Yadav A. (My University, 2025)
The development of bacterial resistance to chemical therapy poses a severe danger to efficacy of treating bacterial infections. One of the key factors for resistance to antimicrobial medications is growth of bacteria in biofilm. Quorum sensing (QS) inhibition was created as an alternative treatment by developing novel anti-biofilm medicines. Cell-cell communication is impeded by QS inhibition, which targets QS signaling pathway. The goal of this work is to develop newer drugs that are effective against Pseudomonas aeruginosa by decreasing QS and acting as anti-biofilm agents. In this investigation, N-(benzo[d]thiazol-2-yl)benzamide/N-(thiazol-2-yl)benzamide derivatives 3a-h were designed and synthesized in good yields. Further, molecular docking analyses revealed that binding affinity values were founded −11.2 to −7.6 kcal/mol that were moderate to good. The physicochemical properties of these prepared compounds were investigated through in-silico method. Molecular dynamic simulation was also used to know better understanding of stability of the protein and ligand complex. Comparing N-(benzo[d]thiazol-2-yl)benzamide 3a to salicylic acid (4.40±0.10) that was utilised as standard for quorum sensing inhibitor, the anti-QS action was found greater for N-(benzo[d]thiazol-2-yl)benzamide 3a (4.67±0.45) than salicylic acid (4.40±0.10). Overall, research results suggested that N-(benzo[d]thiazol-2-yl)benzamide/N-(thiazol-2-yl)benzamide derivatives 3a-h may hold to develop new quorum sensing inhibitors. © 2023 Wiley-VHCA AG, Zurich, Switzerland.